1996
DOI: 10.1107/s010876739609006x
|View full text |Cite
|
Sign up to set email alerts
|

Refined crystal structure of ferredoxin from thermoacidophilic archaeon

Abstract: are necessary for the uridylylation of Pn by UTase!UR.In order to elucidate the potential structural changes which may occur upon ligand binding, Pn has been crystallised with a number of effector ligands including 2-ketoglutarate (2-KG), glutamate and ATP, and ATP in combination with 2-ketoglutarate and glutamate. We anticipate that these structure determinations will provide us with new insights into the way Pn influences the enzymes involved in nitrogen regulation and how its interaction with various ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The zinc atom is liganded by three His residues from the N-terminal domain and one Asp residue from the core domain. This structure (N-terminal extension plus Zn binding site) is absent in eubacterial homologs but is conserved in all other thermoacidophiles (107). Progressive N-terminal deletions and SDM of two of the three His ligands showed that both the N-terminal extension and the zinc atom are important for thermodynamic stability.…”
Section: Metal Bindingmentioning
confidence: 99%
“…The zinc atom is liganded by three His residues from the N-terminal domain and one Asp residue from the core domain. This structure (N-terminal extension plus Zn binding site) is absent in eubacterial homologs but is conserved in all other thermoacidophiles (107). Progressive N-terminal deletions and SDM of two of the three His ligands showed that both the N-terminal extension and the zinc atom are important for thermodynamic stability.…”
Section: Metal Bindingmentioning
confidence: 99%
“…The role of the zinc was deduced to be the assembly of b-strand 5 (comprising b-sheet B) with b-sheet A H + A (Fig. 1) [12,13]. These findings suggest that the N-terminal extra stretch and/or zinc atom in the thermoacidophilic archaeal ferredoxin contribute to the stability of the molecule.…”
mentioning
confidence: 79%
“…strain 7 has a 36-residue extra domain at its N-terminus and a 67-residue core domain carrying two iron±sulfur clusters. A zinc ion is held at the interface of the two domains through tetrahedral coordination of three histidine residues (26, 219 and 234) and one aspartic acid residue (276) [Fujii, T., Hata, Y., Oozeki, M., Moriyama, H., Wakagi, T., Tanaka, N. & Oshima, T. (1997) Biochemistry 36, 1505±1513]. To elucidate the roles of the novel zinc ion and the extra N-terminal domain, a series of truncated mutants was constructed: G1, V12, S17, G23, L31 and V38, which lack residues 0, 11, 16, 22, 30 and 37 starting from the N-terminus, respectively.…”
mentioning
confidence: 99%
“…The family of di-cluster seven-iron ferredoxins [8] (Fd), found among the hyperthermophilic members of the Archaeal order of the Sulfolobales (T opt = 65-85°C), is an example of such proteins. They are small ($100 residues) iron-sulfur proteins containing one [3Fe-4S] 1+/0 (cluster I) and one [4Fe-4S] 2+/1+ cluster (cluster II) [9,10] in addition to a Zn 2+ site [11], which is absent in some ferredoxins of this family lacking the Zn ligands [8,12]. These proteins are usually highly abundant in the cytosol of the host organisms, which allowed EPR studies to establish the biologically active relevance of the [3Fe-4S] 1+/0 centres [9], in opposition to the possibility that they would have arisen from oxidative damage of [4Fe-4S] 2+/1+ clusters [13,14].…”
Section: Introductionmentioning
confidence: 99%